Compensation - Milkovich, George T.; Newman, Jerry M.;Gerhart, Barry (New York : McGraw Hill Education, 2014)
Compensation, 11th Edition, by Milkovich, Newman and Gerhart is the market-leading text in this course area. It offers instructors current research material, in depth discussion of topics, integration of Internet coverage, excellent pedagogy, and a truly engaging writing style. The authors consult with leading businesses, have won teaching awards, and publish in the leading journals. This text examines the strategic choices in managing total compensation. The total compensation model introduced in chapter one serves as an integrating framework throughout the book. The authors discuss major compensation issues in the context of current theory, research, and real-business practices. Milkovich, Newman and Gerhart strive to differentiate between beliefs and opinions from facts and scholarly research. They showcase practices that illustrate new developments in compensation practices as well as established approaches to compensation decisions. Time after time, adopters relay stories of students getting job offers based on the knowledge they learned from this book.
The Pay Model -- Strategy: The Totality of Decisions -- Defining Internal Alignment -- Job Analysis -- Job-Based Structures and Job Evaluation -- Person-Based Structures -- Defining Competitiveness -- Designing Pay Levels, Mix, and Pay Structures -- Pay-for-Performance: The Evidence -- Pay-for-Performance Plans -- Performance Appraisals -- The Benefit Determination Process -- Benefit Options -- Compensation of Special Groups -- Union Role in Wage and Salary Administration -- International Pay Systems -- Government and Legal Issues in Compensation -- Management: Making It Work
Includes index.
Keywords: COMPENSATION MANAGEMENT